PENGARUH METODE PEMBELAJARAN BLENDED LEARNING DAN SELF REGULATED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN EKONOMI: THE INFLUENCE OF BLENDED LEARNING AND SELF-REGULATED LEARNING METHODS ON STUDENTS' CRITICAL THINKING SKILLS IN ECONOMICS SUBJECTS - Efin Nadhiyatul Umami; Siti Nurjanah; Ari Saptono (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This study aims to develop students' critical thinking skills through blended learning methods and self-regulated learning (SRL) strategies for students at the high school level in Economics. The method used in this study is an experimental method with a 2x2 factorial design. The population of this study were all students at SMA Negeri 52 Jakarta and SMA Negeri 83 Jakarta. The sample of this study was students of class XI IPS 3 and XI IPS 4 in each school, where class XI IPS 3 was used as the control class (conventional) and XI IPS 4 as the experimental class (treatment). The research instruments used were pre-test, post-test, and questionnaires. The results of the data analysis used are two-way ANOVA, yielding that there are differences in students' critical thinking skills between conventional classes and blended learning classes, there are differences in students' critical thinking abilities between low and high SRL levels, there are differences in critical thinking abilities between conventional classes and blended learning classes for high SRL students, there are differences in critical thinking skills between conventional classes and blended learning classes for low SRL students, there are differences in critical thinking abilities in conventional classes between high and low SRL students, and there are differences in critical thinking abilities in blended learning classes between SRL students high and low